An examination of contemporary works for the wind, percussion, and brass ensemble: “Motown metal” by Michael Daugherty, “Antiphonies” by Stanley Leonard, and “After the thunderer” by Ira Hearshen - Purcell, Teresa C. (Kansas State University, 2011)
This document is written in support of a conducting recital given in partial fulfillment of the Master’s of Music Education with an Emphasis in Instrumental Conducting at Kansas State University. It encompasses the historical research, theoretical analysis, and rehearsal recommendations and considerations necessary to prepare the selected works for performance. The pieces analyzed are Michael Daugherty’s Motown Metal, Stanley Leonard’s Antiphonies, and Ira Hearshen’s second movement, “after the Thunderer” from Symphony on Themes of John Philip Sousa. I seek to highlight the significance of these works to the literature of their mediums, and show how they are valuable pieces of literature in the contemporary repertoire. In addition, I offer my philosophies on music learning and literature selection as a means to better understand the process entailed in laying the groundwork for successful authentic learning experiences for conductor and students.
Keywords: Music; Band; Daugherty, Michael; Leonard, Stanley; Hearshen, Ira; Score Analysis; Band Score Analysis; Music (0413)